NOVO MÉTODO PARA A PREPARAÇÃO DE FILMES DE Ni(OH)2 NANOESTRUTURADOS - Vileski, Hélcio Marcos (2012)
In the present work a new method for the preparation of thin films of Ni(OH)2 was proposed. The method described in this paper, aims to combine two well-known methods, the sol-gel and Corigan`s method. . Starting from a nickel acetate sol, a cathodic current is applied, leading to the hydrogen evolution and the formation of OHˉ at the metal/solution interface inducing the gelification of the sol and its adhesion to the electrode surface. It was studied the conditions for the deposition in order to obtain uniform, adherent and thin films. The samples were analyzed through DRX and SEM. The electrochemical behavior of the films was studied aiming its application as battery anodes. Through the cyclic voltammetry study, it was observed the formation of the desired phases that exhibit electrochemical behavior quite similar to traditional material. We also demonstrated the possibility of cobalt incorporation for stabilization of the α-phase.